2003
DOI: 10.1128/iai.71.6.3240-3250.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Organization of the N-Terminal Part of the Polymorphic Outer Membrane Proteins 90, 91A, and 91B of Chlamydophila abortus

Abstract: A series of overlapping recombinant antigens, 61 to 74 residues in length, representing polymorphic outer membrane protein 90 (POMP90) of Chlamydophila abortus and two recombinant peptides spanning gene fragment p91Bf99 of POMP91B were assessed by immunoblotting to determine the antigen-binding sites of 20 monoclonal antibodies to POMP90, -91A, and -91B. The epitopes were further restricted by scanning 52 overlapping synthetic 12-mer peptides representing the N-terminal part of POMP90, and the 12-mer epitopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…For other Pmps, positive reacting bands at different sizes could be observed depending on the probe being denatured by boiling or not, which is in agreement with the known temperature‐dependent running behaviour of proteins containing pore‐like beta‐barrel structures (McCafferty et al ., 1995; Christiansen et al ., 1999; Knudsen et al ., 1999). In C. psittaci, only the N‐terminus of Pmps was found to be surface exposed forming a beta helix immunogenic in ovine infection, consistent with the model of a C‐terminal translocator unit incorporated in the OM (Everett and Hatch, 1995; Longbottom et al ., 1998; Vretou et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For other Pmps, positive reacting bands at different sizes could be observed depending on the probe being denatured by boiling or not, which is in agreement with the known temperature‐dependent running behaviour of proteins containing pore‐like beta‐barrel structures (McCafferty et al ., 1995; Christiansen et al ., 1999; Knudsen et al ., 1999). In C. psittaci, only the N‐terminus of Pmps was found to be surface exposed forming a beta helix immunogenic in ovine infection, consistent with the model of a C‐terminal translocator unit incorporated in the OM (Everett and Hatch, 1995; Longbottom et al ., 1998; Vretou et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In detail, after Sec‐dependent delivery into the periplasm, conserved C‐terminal transporter domain spontaneously forms a pore‐like beta‐barrel in the OM through witch the N‐terminal passenger domain leaves the bacterium (Pohlner et al ., 1987; Henderson, et al ., 1998). In case of C. trachomatis and C. psittaci , several Pmps [also called (P)Omps] were shown to be expressed late during the infection cycle and were present in OM‐complexes or on the bacterial surface, eliciting strong immune response in the course of natural infection (Knudsen et al ., 1999; Tanzer et al ., 2001; Tanzer and Hatch, 2001; Vretou et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2, pmp clusters 2 and 3). The products of these genes are part of a larger family of proteins known as the polymorphic membrane proteins (Pmp) that are represented in all of the sequenced Chlamydiaceae genomes (Vretou et al 2003): 9, 21, and 17 pmp genes have been reported within the genome sequences of C. trachomatis/C. muridarum, Cp.…”
Section: Polymorphic Membrane Proteinsmentioning
confidence: 99%
“…Their high immunogenicity is also likely to be significant in the protective immunity conferred by chlamydial outer membrane preparations (Tan et al 1990;Cevenini et al 1991;Longbottom et al 1998b;Vretou et al 2003;Wehrl et al 2004). In total, Cp.…”
Section: Genome Research 635mentioning
confidence: 99%
“…Pmp21 in Fig. 1B ) ( Vandahl et al ., 2001 ; 2002 ; Vretou et al ., 2003 ; Wehrl et al ., 2004 ; Kiselev et al ., 2009 ; Swanson et al ., 2009 ). However, there is no evidence for secretion of Pmps by the AT pathway.…”
Section: Introductionmentioning
confidence: 99%